2014
DOI: 10.1186/1479-5876-12-111
|View full text |Cite
|
Sign up to set email alerts
|

Prednisolone has a positive effect on the kidney but not on the liver of brain dead rats: a potencial role in complement activation

Abstract: BackgroundContradictory evidence has been published on the effects of steroid treatments on the outcomes of kidney and liver transplantation from brain dead (BD) donors. Our study aimed to evaluate this disparity by investigating the effect of prednisolone administration on BD rats.MethodsBD induction was performed in ventilated rats by inflating a Fogarty catheter placed in the epidural space. Prednisolone (22.5 mg/kg) was administered 30 min prior to BD induction. After four hours of determination of BD: ser… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
21
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 44 publications
2
21
0
Order By: Relevance
“…Induction of brain death showed a consistent and uniform pattern in blood pressure with a mean induction time of 32,5 ± 2,5 minutes which is similar to our previous publications [ 31 ]. After brain death induction all animals were kept with a mean arterial pressure of above 80 mmHg during the remainder of the experiment ( Figure 1 ).…”
Section: Resultssupporting
confidence: 89%
See 3 more Smart Citations
“…Induction of brain death showed a consistent and uniform pattern in blood pressure with a mean induction time of 32,5 ± 2,5 minutes which is similar to our previous publications [ 31 ]. After brain death induction all animals were kept with a mean arterial pressure of above 80 mmHg during the remainder of the experiment ( Figure 1 ).…”
Section: Resultssupporting
confidence: 89%
“…In a previous study we showed that prednisolone administered before the induction of brain death in fact reduced inflammation measured by IL-6 plasma levels and renal and liver expression of proinflammatory cytokines like IL-6, IL-1β, MCP-1 , and TNF-α . Interestingly prednisolone pretreatment did improve renal function measured by creatinine plasma levels but did not improve liver cellular injury measured by AST, ALT, and LDH plasma levels [ 31 ]. We think that this differing effect may be related with the persistence of complement activation ( C3 ) in the liver and downregulation of protective cellular mechanisms such as heat shock proteins.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Intraportal infusion of steroids and prostaglandin E1 administrated for ABO incompatible cases during the first 2 weeks after transplantation could have played a role; however, the sample size was very small to draw a definite conclusion. Prostaglandin E1 is a potent vasodilator and may potentially protect the kidney; however, the positive effect of steroids on kidney function has been shown in only animal studies at the time of writing …”
Section: Discussionmentioning
confidence: 99%